2014
DOI: 10.4103/2141-9248.144876
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status and some variables among pregnant women in a Nigeria tertiary institution

Abstract: Background:Gingival changes during pregnancy have been well-documented. The prevalence of gingivitis in pregnant women has reportedly ranged from 30% to 100%. Increase in both the rate of estrogen metabolism and synthesis of prostaglandins by the gingiva contributed to the gingival changes observed during pregnancy. In effect increased prevalence of dental caries, gingivitis, periodontitis and tooth mobility may be encountered in pregnancy.Aim:The purpose of the study was to determine the association of some v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
4
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 18 publications
2
39
4
7
Order By: Relevance
“…29 This may be due to the fact that the sample in the study consisted mostly of young women. However, this result is in contrast to other studies 22,37 in which the authors have suggested that aging is a natural process which results in changes in host immunity which may cause the loss of periodontal support tissue. 29…”
Section: Agecontrasting
confidence: 99%
See 2 more Smart Citations
“…29 This may be due to the fact that the sample in the study consisted mostly of young women. However, this result is in contrast to other studies 22,37 in which the authors have suggested that aging is a natural process which results in changes in host immunity which may cause the loss of periodontal support tissue. 29…”
Section: Agecontrasting
confidence: 99%
“…44 This was interpreted as accumulated tissue destruction across time rather than an intrinsic parity related abnormality. Contradicting result has been reported by Onigbinde et al 37…”
Section: Paritymentioning
confidence: 55%
See 1 more Smart Citation
“…So the identification of the risk factors for periodontitis during pregnancy can help guide and establish early treatment, which can lead to the avoidance of the possible adverse effects of this disease on pregnancy. [1][2][3] During pregnancy, progesterone levels increase 10-folds and estrogen levels 30-folds compared to those observed on the menstrual cycle due to their continuous production. Such fluctuating female hormone levels can change conditions inside the mouth and allow bacterial growth as а result of decreased saliva, such bacteria use the eaten sugar to make acid, that acid can destroy the enamel (the protective coating of teeth) causing tooth decay and many dental problems as dental caries that caused by the progress of carious pathogens and increased de mineralization of tooth.…”
Section: Introductionmentioning
confidence: 96%
“…This survey thus revealed that misconceptions still exist amongst school teachers, this may contribute to the increasing prevalence of periodontal disease in the population. Also in another study by Onigbinde et al(2014), it was found that prevalence of periodontal disease ranges from 30-100%. The study further reiterated that this was as a result of increase in estrogen metabolism and synthesis of prostaglandin that occurs during pregnancy thus further worsening dental caries, gingivitis, and periodontitis.…”
Section: Introductionmentioning
confidence: 99%